Challenges and opportunities for Australian local governments in governing climate change adaptation and disaster risk reduction integration. Issue 3 (11th June 2018) - Forino, Giuseppe; Von Meding, Jason; Brewer, Graham John
Abstract : Purpose: This paper aims to explore challenges and opportunities for Australian local governments (LGs) in governance of climate change adaptation (CCA) and disaster risk reduction (DRR) integration. Design/methodology/approach: The paper identifies three Australian LGs which are subjected to potential climate change-related hazards. Semi-structured interviews with staff officers of the selected LGs and supporting organizations have been conducted to collect and analyze primary data. Findings: The findings reveal that emerging challenges in governance of CCA and DRR integration include the political sensitiveness of climate change, uncertainty and standstill because of the vagueness by higher government levels, competing interests between LGs' departments and communication breakdowns because of scepticism and the use of jargon. Meanwhile, the findings reveal that emerging opportunities include the promotion of participation mechanisms in planning, the creation of partnerships with local stakeholders and the use of coordination organizations and platforms. Exploring these challenges and opportunities represents a key step to strengthen governance mechanisms at a local level. Research limitations/implications: The paper is based on a limited number (3) of Australian case studies with a limited number (15) of interviews. Further insights could be gained by analyzing more Australian LGs, involving a higher number of participants, and by using complementary research methods and data (survey and questionnaires) about experiences of other local stakeholders. Originality/value: The paper is one of the few exploring challenges and opportunities of Australian LGs in governance of CCA and DRR integration in Australia and discusses them in terms of the potential to strengthen governance mechanisms within Australian LGs.